Utilization of Multitemporal Land Cover Data and GIS for SWAT-Based Sedimentation and Runoff Modeling in the Lasolo Watershed, Indonesia - YASIDI, Farid; KHAKHIM, Nurul; MARDIATNO, Djati; KURNIAWAN, Agung (Journal of Environmental Management and Tourism, 2023)
Sedimentation and surface runoff are two vital processes occurring in a watershed, and calculating the constituent transports of sediments and surface water is the initial step in planning. This research was intended to model surface runoff and sedimentation temporally (2008, 2013, 2018, and 2021) on hydrological response unit (HRU) and subwatershed levels for the Lasolo Watershed in Southeast Sulawesi, Indonesia. Soil and Water Assessment Tool (SWAT), a physically based hydrological modeling instrument, was selected for the simulation using these input data: SRTM DEM, land cover, soil type, and several climatological data sourced from ERA5, NASA GLDAS, and the NASA POWER Project. Results showed fluctuating surface runoff and sediment yield throughout the simulation time frame. The mean surface runoff peaked at a capacity of 216.6 mm/year in 2013, and the mean sediment yield was also the highest this year, 10.8 tonnes/ha/year. In 2021, there was a significant reduction to 18.2 mm/year for surface runoff and 0.91 tonnes/ha/year for sediment yield. Simulations suggested that the watershed’s surface runoff capacity is directly proportional to the sediment yield produced.